Adipose tissue displays trophic properties on normal lung cellular components without promoting cancer cells growth12. Issue 6 (25th February 2013) - Andriani, F.; Facchinetti, F.; Furia, S.; Roz, L.; Bursomanno, S.; Bertolini, G.; Carniti, C.; Sozzi, G.; Pastorino, U.
Abstract Surgical removal is the mainstay for early lung cancer treatment and persistent air leaks represent one of the most common clinical complications after lung surgery. Adipose tissue transplantation has been proposed as a new strategy for regenerative therapy after breast cancer surgery; however its efficacy and safety of lung tissue healing after lung resections are unknown. The purpose of this study was to test the biological activity of adipose tissue to facilitate lung tissue healing and evaluate its effect on cancer cells growth, thus providing insight for a possible clinical application. Different in vitro cellular models were used to prove the potential biologic effect of autologous fat tissue (AFT) in repairing injured lung tissue, and in vivo xenograft models were used to evaluate tumor promoting potential of AFT on putative residual cancer cells. Treatment of both embryonic (WI‐38) and adult lung fibroblasts and of normal bronchial epithelial cells (HBEC‐KT) with AFT samples, harvested from subcutaneous tissue layer of 20 patients undergoing pulmonary metastasectomy, improved wound healing and cell proliferation indicating a trophic effect on both mesenchymal and epithelial cell types. Conversely AFT‐conditioned medium was unable to stimulate in vitro proliferation of a lung adenocarcinoma reporter cellular system (A549). Moreover, co‐injection of AFT and A549 cells in nude mice did not promote engraftment and progression of A549 cells. These preclinical findings provide preliminary evidence on the potential efficacy of AFT to accelerate lung tissue repair without undesired tumor promoting effects on putative residual cancer cells. J. Cell. Physiol. 228: 1166–1173, 2013. © 2012 Wiley Periodicals, Inc.